2021
DOI: 10.1038/s41598-021-87265-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photobiomodulation therapy on painful temporomandibular disorders

Abstract: To evaluate the effect of photobiomodulation therapy (PBMT) on painful temporomandibular disorders (TMD) patients in a randomized, double-blinded, placebo-controlled manner. Participants were divided into a masseter myalgia group (n = 88) and a temporomandibular joint (TMJ) arthralgia group (n = 87) according to the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD). Both groups randomly received PBMT or placebo treatment once a day for 7 consecutive days, one session. The PBMT was applied with a gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…As for the treatment outcomes observed, 12/20 studies (60%) [59][60][61][62][63][64]66,67,70,[73][74][75]] presented a positive result, while 8/20 (40%) [65,68,69,71,72,[76][77][78] showed no difference from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As for the treatment outcomes observed, 12/20 studies (60%) [59][60][61][62][63][64]66,67,70,[73][74][75]] presented a positive result, while 8/20 (40%) [65,68,69,71,72,[76][77][78] showed no difference from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…All of the included studies provided information on pain intensity except one. 48 Fifteen RCTs evaluated MMO, 1,25,34,36,38,40,41,44,46,[50][51][52]54,57,61 two evaluated AMMO and PMMO, 35,60 ten evaluated LM, 1,24,25,34,36,38,46,54,60,61 four evaluated PM, 1,25,38,46 nine evaluated PPT, 25,39,40,42,46,50,52,53,60,6 4 five evaluated EMG activity, 37,39,40,48,52 and five evaluated sounds of TMJ. 24,31,34,44,51 Twenty-seven studies out of 39 showed a reduction in pain intensity in the PBMT groups in comparison with the control groups.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…24,31,34,44,51 Twenty-seven studies out of 39 showed a reduction in pain intensity in the PBMT groups in comparison with the control groups. 1,24,26,[29][30][31][33][34][35][36][37][38][40][41][42][43][45][46][47]49,52,[55][56][57][58]60,61 Among the RCTs that reported MMO, seven studies 34,36,38,41,46,54,61 showed a greater MMO in the PBMT groups compared to the placebo groups; while others showed no difference. Also, AMMO and PMMO were reported to be greater in the PBMT groups.…”
Section: Assessment Methodsmentioning
confidence: 99%
See 2 more Smart Citations